Variance reduction with Monte Carlo estimates of error rates in multivariate classification - Claus Weihs; Giorgio Calzolari; Michael C. Röhl (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
In this paper, control variates are proposed to speed up Monte Carlo Simulations to estimate expected error rates in multivariate classification.
Keywords: 519; classification; control variates; error rate; Monte Carlo Simulation; variance reduction